1996
DOI: 10.1046/j.1464-410x.1996.14624.x
|View full text |Cite
|
Sign up to set email alerts
|

Male reproductive function in uraemia: efficacy of haemodialysis and renal transplantation

Abstract: Objective To evaluate the impact of maintenance haemodialysis and live‐related renal transplantation on the reproductive potential of men with end‐stage renal disease. Patients and methods The plasma levels of testosterone, follicle‐stimulating hormone (FSH) and luteinizing hormone (LH) were determined, and semen analysed, in 19 men (22–41 years old) with advanced uraemia after 6 months of dialysis and again 6 months after renal transplantation. Eight patients who had azoospermia or severe oligospermia underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 6 publications
2
77
0
7
Order By: Relevance
“…A decreased volume of ejaculate combined with low or complete azoospermia and a low percentage of motility has been shown in semen analysis (32). Compared with other causes of severe primary testicular lesions, the Leydig and Sertoli cells show little evidence of hypertrophy or hyperplasia, probably due to a defect in their hormonal regulation.…”
Section: Disorders Associated With Testicular Failurementioning
confidence: 98%
See 1 more Smart Citation
“…A decreased volume of ejaculate combined with low or complete azoospermia and a low percentage of motility has been shown in semen analysis (32). Compared with other causes of severe primary testicular lesions, the Leydig and Sertoli cells show little evidence of hypertrophy or hyperplasia, probably due to a defect in their hormonal regulation.…”
Section: Disorders Associated With Testicular Failurementioning
confidence: 98%
“…The plasma FSH levels tend to be highest in those uremic patients with the most severe damage to seminiferous tubules and presumably the lowest levels of inhibin. It has been reported that high FSH levels may portend a poor prognosis for recovery of spermatogenic function after renal transplantation (32). The administration of clomiphene to uremic patients leads to an appropriate rise in the levels of both LH and FSH, suggesting that the negative feedback control on the hypothalamus is intact and that the storage and release of gonadotropins by the pituitary is normal (34).…”
Section: Disorders Associated With Testicular Failurementioning
confidence: 99%
“…The plasma concentration of the pituitary gonadotropin luteinizing hormone (LH) is elevated probably as a result of the decreased release of testosterone from the Leydig cells and the consequent loss of normal negative feedback. In addition the metabolic clearance rate of LH is reduced and it is not corrected by dialysis [16] . In uremic subjects disturbances in LH secretion has been observed but it is not known whether this is the result of a change in GnRH release from the hypothalamus or a change in the responsiveness of the pituitary.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Chronic renal failure (CRF) is associated with impaired spermatogenesis and testicular damage, often leading to infertility. A decreased volume of ejaculate combined with low or complete azoospermia and a low percentage of motility has been shown in semen analysis [27]. Leydig and Sertoli cells are prone to defects in their hormonal regulation.…”
Section: Introductionmentioning
confidence: 98%
“…The exact pathophysiological mechanism involved in CRF-induced testicular damage is not fully understood. Haemodialysis patients have reduced testicular volume, indicating impaired spermatogenesis [41], however, recovery of hormonal and spermatogenic abnormalities occur after renal transplantation [27,39]. Spermatozoa obtained from uremic patients show improved ultrastructural features after renal transplantation, and a low dose of immunosuppressant is suggested to prevent degenerating effects of immunosuppressive therapy on seminiferous epithelia [42].…”
mentioning
confidence: 99%